Simple two-step gelation process to strengthen 3D printed carboxy methyl cellulose gels - Rajput, Tejas; Sathe, Asmi; Gopal, Animesh; Sharma, Aakash; Shanmuganathan, Kadhiravan (Cellulose, 2026)
Carboxymethyl cellulose (CMC) is a water-soluble cellulose ether that is widely utilized in hydrogel applications due to its exceptional water absorption and biocompatibility. This study reports a simple two step strategy to make mechanically robust CMC gels without any additional chemical crosslinkers and how it could be leveraged to strengthen 3D printed CMC gels. These hydrogels, prepared through acid-induced gelation followed by freeze-thawing, exhibited a compressive modulus of 12.4 +/- 0.92 kPa and a compressive strength of 491.0 +/- 18.1 kPa. They could be leveraged for strengthening 3D printing hydrogels of intricate shapes by direct ink writing. Small amplitude oscillatory shear (SAOS) tests indicated an order of magnitude higher storage modulus for freeze-thawed gels (FC) as compared to only acid-induced CMC gels (HCMC). Nonetheless, stress relaxation experiments revealed that FC, as well as HCMC gels, relax at similar time scales. FC gels exhibited clear birefringence under crossed polarizers, indicating molecular ordering that is consistent with the presence of ordered/crystalline domains. Such ordered domains likely contribute to the higher elastic modulus and compressive strength observed in FC gels as compared to HCMC gels.
Keywords: 3D printing; Carboxymethyl cellulose; cellulose; Gels

Vanillin-based recyclable thermosets and their glass fiber reinforced composites - Veetil, Ashwani Puthiya; Ravikumar, Aniruddha; Rajput, Tejas; Singh, Aman Kumar; Thakur, Tamanna; Krishna, Abhijith; Pol, Harshawardhan; Shanmuganathan, Kadhiravan; Asha, S. K. (Macromolecular Chemistry and Physics, 2026)
The accumulation of end-of-life plastic materials and composite reinforcement waste materials has brought much attention to developing sustainable alternatives and their re-processability. Incorporating covalent adaptable networks (CANs) into the crosslinked network bridges the concept of reversibility into the otherwise conventional non-reversible networks. This study investigates the structure-property relation in two reversible hardener systems derived from vanillin using Schiff base chemistry. The ``CAN'' systems were synthesized by condensation of vanillin with two amines, 4,4'-oxydianiline and tris(2-aminoethyl)amine, respectively, to form Va_ODA and Va_TAEA. The epoxy thermosets exhibited glass transition temperatures (T-g) of 125 degrees C and 115 degrees C, respectively, for Va_ODA and Va_TAEA, which is superior to most reversible vanillin-based systems reported. The vitrimer-thermosets exhibited promising mechanical and thermal properties, and reshaping abilities as a function of applied temperatures, indicating the dynamic nature of linkages. Chemical degradability was demonstrated by heating to 80 degrees C for 12 h in aqueous acidic medium or excess amine. The fabricated glass fiber composites exhibited good mechanical properties with tensile strength of 361 MPa and degradability in acetic acid/water mixture with a fiber recovery of >98 %. The recovered glass fiber exhibited almost similar tensile strength as the virgin glass fiber, demonstrating its potential reusability. The epoxy vitrimers underwent mechanical reprocessing through hot-pressing, as well as chemical reprocessing via 3D printing and by regeneration of imine bonds to form an epoxy resin.
Keywords: 3D printing; covalent adaptable network; re-processability; Schiff base; Vanillin